Structural and optical properties of hydroxylfunctionalized graphene quantum dots-based thin film and its potential sensing for ferric ion using surface plasmon resonance - Anas, Nur Ain Asyiqin (2020)
As a new promising carbonic nanomaterial with a lot of outstanding advantages, graphene quantum dots (GQDs) opened up a new field for the development of excellent sensors. Herein, the preparation of hydroxyl-functionalized graphene quantum dots (HGQDs) based thin film with different materials that are chitosan and cetyltrimethylammonium bromide (CTAB) have been described namely chitosan/hydroxyl-functionalized graphene quantum dots (Cs/HGQDs) thin film and cetyltrimethylammonium bromide/hydroxyl-functionalized graphene quantum dots (CTAB/HGQDs) thin film. The Cs/HGQDs and CTAB/HGQDs were deposited homogenously using the spin coating technique. The synthesized thin films were then characterized using Fourier transform infrared spectroscopy (FTIR) to confirm the existence of functional groups in the composites such as hydroxyl, carboxyl, and carboxylic acid. From the atomic force microscope (AFM) analysis, the addition of chitosan and CTAB increased the roughness of the thin films. Meanwhile, the optical properties of the thin films were studied using UV-Vis absorption spectroscopy and photoluminescence (PL) spectroscopy. The absorbance peaks of Cs/HGQDs and CTAB/HGQDs thin films can be observed around the wavelength of 270 nm to 300 nm with optical band gap values of 3.80 eV and 4.16 eV, respectively. Moreover, the intensity of PL spectra for both thin films were noticed around the wavelength of 420 nm to 450 nm. The development of optical sensors for heavy metal ions detection has been rapidly growing. However, the current methods suffer limitations which then led to the emergence of an outstanding technique called surface plasmon resonance (SPR) spectroscopy. In this study, the as developed thin films have been incorporated with SPR for the detection of ferric ion (Fe3+). The sensors produce positive responses upon exposure to Fe3+ of various concentration. At lower Fe3+ concentration, the CTAB/HGQDs thin film showed higher sensitivity equals to 29.886° ppm-1 compared to Cs/HGQDs with value of 0.114° ppm-1. Subsequently, the Langmuir isotherm model yielded higher binding affinity constant, K for CTAB/HGQDs thin film than Cs/HGQDs thin film with values of 221.729 ppm-1 and 5.79 ppm-1, respectively. Thus, both thin films show potential for the detection of Fe3+.